ChemInform Abstract: Ca3ZnGeO2[Ge4O12]: A Ca—Zn Germanate Related to the Mineral Taikanite. Issue 10 (March 2015) - Redhammer, Guenther J.
Abstract The title compound is obtained as a by‐product upon sintering of phase‐pure synthetic pyroxene‐type CaCu0.95Zn0.05Ge2O6 (open Pt tube, 1283 K).